Normative values of the Balance Evaluation System Test (BESTest), Mini-BESTest, Brief-BESTest, Timed Up and Go Test and Usual Gait Speed in healthy older Portuguese people - Almeida, Sara Isabel Lebre de (2017)
Objective: This study aimed to establish age and gender-related normative values for the Balance Evaluation System Test (BESTest), Mini-BESTest, Brief-BESTest, Timed Up and Go (TUG) test and Usual Gait Speed (UGS) for Portuguese healthy older people aged 60 to 89 years. Design: An exploratory cross-sectional study was conducted. Local: Portugal. Population: Portuguese healthy older people aged 60 to 89 years. Methods: Participants were recruited from the community. Socio-demographic, anthropometric and general clinical data were collected with a structured questionnaire based on the International Classification of Functioning, Disability and Health. Balance was assessed with the BESTest, Mini-BESTest and Brief-BESTest, mobility with the TUG and gait speed with the six meters UGS. Normative scores were reported by age decades (60-69; 70-79 and 80-89 years old) and gender. Results: One hundred and thirteen healthy older people (75.8±8.9 years; 70.5% female) participated in this study. Mean scores for the BESTest (86.5±15.6; 82.6±14.5; 72.6±15.0), Mini-BESTest (22.4±6.3; 21.6±5.9; 16.2±6.2), Brief-BESTest (17.5±6.3; 16.0±6.0; 10.2±5.5) and UGS (122.3±46.8cm/s; 116.6±47.3cm/s; 73.8±32.6cm/s) decreased whereas TUG (8.9±2.8s; 9.5±4.0s; 16.8±5.3s) increased as age advanced. Female presented worse results than male. Mean scores of all measures were significantly different among age and gender groups (p